PENGARUH PEMBERIAN SARI KURMA TERHADAP KENAIKAN HEMOGLOBN PADA REMAJA - Astik Umiyah; Selvia Nurul Qomari; Dina Al Habsyi (Poltekkes Kemenkes Medan, 2021)
Women have a high risk of suffering from anemia, especially in teenage girl. Anemia can affect teenage girl growth and development, the body during infancy is easily infected, decreased enthusiasm for learning. The purpose of this research is to know the effect of giving palm juice to the increase in hemoglobin levels in teenage girl who have anemia in dorm Ma’had Aly Pondok Pesantren Salafiyah Syafi’iyah Sukorejo Situbondo 2018. This study used a pre experiment design with a sample of 35 respondents who met the iclusion criteria with a total sampling technique. The treatment was given date palm juice to 35 respondents. Analysis was done using paired sample T test. Statistical test result show significant value (p< 0,05) the meaning is that there is an effecf of giving palm juice to the increase in respondents who have anemia. Giving date palm juice can increase hemoglobin levels because the nutrient content contained in date palm juice is very effective in raising hemoglobin levels in the blood. Expect that the provision of date palm juice still needs to be continued, and the need for counseling to teenage girl in order to increase knowledge about nutrition and health and food intake.